Imitation - Theory and Experimental Evidence - Jose Alpesteguia; Steffen Huck; Jörg Oechssler (Center for Economic Studies and ifo Institute (CESifo), 2003)
We introduce a generalized theoretical approach to study imitation models and subject themodels to rigorous experimental testing. In our theoretical analysis we find that the differentpredictions of previous imitation models are due to different informational assumptions, notto different behavioral rules. It is more important whom one imitates rather than how. In alaboratory experiment we test the different theories by systematically varying informationconditions. We find that the generalized imitation model predicts the differences betweentreatments well. The data also provide support for imitation on the individual level, both interms of choice and in terms of perception. But imitation is not unconditional. Ratherindividuals' propensity to imitate more successful actions is increasing in payoff differences.
Keywords: 330; evolutionary game theory; stochastic stability; imitation; Cournot markets; experiments